Social Capital: Trust Building as A Strategy of Developing Madrasa (A Case Study at MI Istiqomah Sambas Purbalingga) - Munjin Munjin (Ijtimā'iyya, 2018)
The developent of madrasa should not depend on financial capital, like infrastructure and media. There is another variabel which has an important role, that is social capital. If the two variables are maximally used by the headmaster, madrasah will increase rapidly, moreover that madrasa has geneologically the big mass basis. Practically, there are many madrasas that have that two modals, but only few of them can manage to be a power to develop madrasa.  One of them is Madrasa Istiqomah Sambas Purbalingga, which uses social capital, espesially trust, as a strategi in developing madrasa, despite the fact that it does not stand under a certain religious organization.  So, the research question of this study is how MI Istiqomah Sambas Purbalingga build and manage the social capital of trust. In addition, this reseacrh will find out a good strategy in developing madrasa and strengthening the social capital. To collect data, the writer performed observation and interviewed some informants and collect some needed documentation. The collected data were then analyzed and connected to the theory used and finally was made conclusion. The conclusion of this research is that social capital of trust was built by philosophical, practical and institutional trust. The inclusive character of madrasa can also help to build trust.